Peran Ranting 'Aisyiyah Gedong Dalam Meningkatkan Pendidikan Akhlak Di Kelurahan Gedong Kecamatan Karanganyar Kabupaten Karanganyar Periode 2010-2015 - Askariyah, Anis, Dr. Imron Rosyadi, M.Ag (2016)
'Aisyiyah is one of autonomous organizations in Muhammadiyah. This organization was founded as supporting effort of Dakwah movement of Muhammadiyah. Muhammadiyah put more focus on general isuues, meanwhile, Aisyiah fosusses on women' issues. The initial goal was to eradicate ignorance among women so that they can get ahead and equal to the progress of men.'Aisyiyah as an organization that cares about the guidance and moral education can face the weaknesses and threats that will damage generation's morals, especially the youth of Islam. Increasing of the program monitoring and evaluation is thing to do so that the program can be run effectively and efficiently and get maximum results. This study aimed to describe and analyze the role of 'Aisyiyah Gedong in moral education in society. Formulation of the research issue How the role of twig in 'aisyiyah Gedong to improving education of akhlak?. This research belongs to field research applying qualitative approach, which describes and analyzes the role of 'Aisyiyah Gedong in moral education in society Methods of data collection were interviews, documentation and observation. The analysis of data used qualitative description, which describes the data that has been collected and analyzed and conclusions drawn by the deductive method is the cornerstone of departure sourced from thought and theory. After the authors conducted research on 'Aisyiyah Gedong and its role in improving the moral education, the writer took some conclusions that the leaders of 'Aisyiyah Gedong cared and took a very important role in moral education. The role of the branches 'Aisyiyah building to improve moral education of God manifested in the construction of woman and the construction of harmonious family through education, while the increase in moral education to the community created in improving social welfare sympathize orphans and develop the potential of cadies capable of providing good role models.